If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + 10 = 3w + -10 Reorder the terms: 10 + w = 3w + -10 Reorder the terms: 10 + w = -10 + 3w Solving 10 + w = -10 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 10 + w + -3w = -10 + 3w + -3w Combine like terms: w + -3w = -2w 10 + -2w = -10 + 3w + -3w Combine like terms: 3w + -3w = 0 10 + -2w = -10 + 0 10 + -2w = -10 Add '-10' to each side of the equation. 10 + -10 + -2w = -10 + -10 Combine like terms: 10 + -10 = 0 0 + -2w = -10 + -10 -2w = -10 + -10 Combine like terms: -10 + -10 = -20 -2w = -20 Divide each side by '-2'. w = 10 Simplifying w = 10
| 4(-5+7a)=26+5a | | 9/28•19/54 | | (14n/3)=8(n-14) | | -25/28•(-21) | | 2X-(5X+9)=8-3X | | 1+6(x-4)=2-8(x-9) | | (x-6)/4=20 | | 4(4+4k)=-32+8k | | -297=4+7(-5v-8) | | 10+2-21=0 | | x-6/4=20 | | ((T^2+3t-8)-(t^2-2t+6))(t-4)=0 | | 7+20x+12x= | | 3-9t=-10t | | 4X+48=8(X+6)-4X | | 252=4(-1-8v) | | -3-8p=-9p+6 | | 3a+3=9+a | | 4x-3(4-3x)=5(x-4)-40 | | Y/3=40 | | 17/6=34/x | | 2+3(x+5)=38 | | 154=7(7k+1) | | -4(n-6)=n+6 | | 5+8(x-3)=4-4(x-3) | | 4(3Z-1)-5(Z+4)=5(Z+1) | | 2/3=1/9(27) | | -27a-42=a+98 | | T/0.16=0.5/0.4 | | 110=7p-8(2-7p) | | 4(5x-4)=4x+17 | | -3-8=-9+6 |